The development of an assistive technology device/orthoprosthesis for the rehabilitation of patients with leprosy and the presence of a claw hand and/or bone resorption (Research, Society and Development, 2021)
This article seeks to present the development of a low-cost orthoprosthesis in order to assist the manual functions of individuals affected by leprosy with claw hand sequelae with or without bone resorption and evaluate its cost-benefit. This process took place through the use of the principles of levers for the construction of the mechanics of the device, and alternative materials such as fiberglass, natural leather and galvanized sheet were also used for its cheapening and manufacture. From the use of these, it was possible to develop a product that presents excellent mechanical benefit, combined with a reduced cost and with a compact and simplified design, which can promote the rehabilitation and return of the performance of activities of daily living of individuals affected by leprosy who have sequelae from hand to claw and/or bone resorption. When compared to gold standard means of manufacturing, such as 3D printing, it was still competitive with these, having manufacturing time, reducing the effort required for their use and the use of low-cost materials as the greatest differential in relation to the others.